PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Siti Juwaeriah; Muhyani Muhyani; Gunawan Ikhtiono (Attadib: Journal of Elementary Education, 2018)
This study aims to determine the effect of cooperative learning model of jigsaw type to the motivation of learning and student learning outcomes in the fourth grade mathematics course SDIT Al-Hidayah Cibinong Bogor Regency. The method used in this research is Quasi Eksperimen research method which is part of quantitative method, and has its own characteristic especially with the existence of control group and experiment group. In this study the selection of samples was not done randomly but deliberately chosen by the researchers. Instruments used in this research are: test, observation, questionnaire and documentation. The results showed that in the experimental class the value of t arithmetic> t table (2.158> 2.00), based on the acquisition value can be concluded that t count> t table (2.158> 2.00) Ha is accepted. This means that in this experimental class the value of the test after using the jigsaw type cooperative learning model is higher than the test before using the jigsaw learning model. For student learning motivation based on tables and recapitulation of questionnaire data can be seen that the result of control class with an average of 29.03 and experimental class with an average of 29.59. So it can be concluded that there is a significant influence between learning motivation and student learning outcomes taught by cooperative learning model type jigsaw with conventional learning model.